1988
DOI: 10.1177/00220345880670100501
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Demonstration of Carbonic Anhydrase Activity in the Odontogenic Cells of the Rat Incisor

Abstract: Aldehyde-fixed, EDTA-demineralized frozen sections of the rat maxillary incisor were histochemically stained for carbonic anhydrase activity, by use of Hansson's method. Intense staining was observed in the odontoblasts, all types of epithelial cells of enamel organ in the maturation zone, cementoblasts, and the cells of the lingual dental sac. Less intense but consistent staining was observed in all types of epithelial cells of odontogenic origin directly facing the pulp and pulp cells adjacent to the odontob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 8 publications
(15 reference statements)
3
25
1
Order By: Relevance
“…Sugimoto et al (1988) have demonstrated CA activity in rat ameloblasts and papillary cells of the maturation stage histochemically, and their results agree with those described in the present study. Our immunohistochemical studies further confirmed that the CAII signal in these cells was constant until these cells fused with the gingival epithelium.…”
Section: Figs 3-6supporting
confidence: 93%
See 4 more Smart Citations
“…Sugimoto et al (1988) have demonstrated CA activity in rat ameloblasts and papillary cells of the maturation stage histochemically, and their results agree with those described in the present study. Our immunohistochemical studies further confirmed that the CAII signal in these cells was constant until these cells fused with the gingival epithelium.…”
Section: Figs 3-6supporting
confidence: 93%
“…Hansson's histochemical procedure detects CA activity in tissues. This method has been used to localize CA in the rat incisor (Dogterom and Bronckers 1983;Sugimoto et al 1988), although it does not discriminate CA isozymes and its specificity has been questioned (Churg 1973;Lönnerholm 1984;Ridderstråle 1991). Our immunohistochemical observations were similar to the histochemical results.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations